Matrilineal System Of Rights Division Inheritance According To Traditional Inheritance Law, Islamic Inheritance Law And The Civil Code - Jamburi, Ahmat; Muhibbin, Moh. (Universitas Islam Malang, 2024)
Abstract: Inheritance law is one part of civil law as a whole and is the smallest part of family law. Inheritance law is closely related to the scope of human life, because every human being will definitely experience a legal event called death. In the territory of the Unitary State of the Republic of Indonesia, various inheritance law systems apply, namely customary inheritance law, Islamic inheritance law and Western inheritance law as stated in the Burgerlijk Wetboek (BW). The family system in Indonesian society focuses on the lineage system. In general, there are three kinship systems, namely the patrilineal system (found in communities in Tanah Gayo, Alas, Batak, Ambon, Irian Jaya, Timor and Bali), the matrilineal system (found in the Minangkabau area), and the bilateral or parental system (found in regions include: Java, Madura, East Sumatra, Riau, Aceh, South Sumatra, all of Kalimantan, all of Sulawesi, Ternate and Lombok). The inheritance distribution system according to Minangkabau customary law is based on a descent system drawn from the mother's line, namely a matrilineal inheritance system where the position of children is inherited. Wo men are the successors, but the heirs are all children, male and female, who come from the mother's assets.